Diffusion–advection process modeling of organochlorine pesticides in rivers. (2nd January 2023) - Cardenas, S.; Márquez, A.; Guevara, E.
Abstract : This paper deals with the diffusion–advection process modeling of organochlorine pesticides (OCPs ) dissolved in a topical river. The novelty consists of proposing mathematical expressions to estimate the physical coefficients (molecular diffusion, advective diffusion, partition) and biochemical coefficients (substrate utilization rate) of OCPs advection–diffusion processes combined to OCPs biochemical transformation processes. The OCPs involved were DDTs (p.p'-DDT, o.p'-DDT, p.p'-DDD, p.p'-DDE, o.p'-DDE) and DRINs (Aldrin, Dieldrin and Endrin). Four scenarios for simulating the OCPs transport were calibrated: (1) molecular diffusion, (2) biochemical transformation, (3) advection–diffusion and (4) a combination of advection–diffusion, biochemical transformation and sorption/desorption processes. The evaluated scenarios predicted with a good approach to the OCPs 's spatio-temporal distribution with a prediction capability within an interval until 1.5 standard deviation with respect to the mean of difference between observed and simulated OCPs The scenario N°4 associated to a coupled model offered a suitable prediction of processes for a tropical river.